KARAKTERISTIK FISIK TANAMAN DAN MUTU LATEKS KARET (HEVEA BRASILLIENSIS MULL. ARG) DATARAN RENDAH DAN DATARAN TINGGI - Ridawati Marpaung; Rudi Hartawan (Jurnal Ilmiah Universitas Batanghari Jambi, 2014)
This study aims to determine the purpose of research to look at the physical characteristics of the plant and the quality of latex rubber (Hevea brasilliensisMull. Arg) lowlands and highlands. This study was conducted have been carried out in low-lying areas (Tables cottage village, District Mestong, Muaro Jambi) with altitude <200 m above sea level (asl), while the highlands (In the village of Khajuraho), District of Batang Merangi, District Kerinci with altitude> 700 m above sea level (asl). This research was carried out for 3 monthsPlant samples used in this study is the people's rubber plant clone 24. BPM object taken is lowland rubber plant with a height of <200 m asl and highlands> 700 m asl, rubber plants have aged> 7 years (already in production). Experiments conducted using survey method in community gardens and quality testing laboratory tested latex UPTD BPSMB Jambi.The parameters observed were: Physical Plant consists of the calculation of the number of branches, leaf dry weight measurement (gcmˉ²), and measurement Trunk circumference (cm). While measuring the quality latex rubber tnaman consists of: Testing the dry rubber content, the determination of levels of Dirt Lteks, the determination of levels of Abu. The researcher also the determination of point coordinates and Altitude, observations Age Start Produce, and pengukuan production and productivity. Data field observations conductedBased on field observations in the average number of branches of the rubber plant lowland and highland 19.45 8.4. The average dry weight of plant leaf heavier rubber plateau is 0.006412 g cm2 compared to the dry weight of the rubber plant leaves lowland is 0.004187 g cm2. . The girth between lowland rubber plant is 65.05 cm larger than the girth of rubber plants plateau 43.97 cm, quality latex rubber plant lowland better than latex rubber plants plateau. Lowland rubber plant at an altitude of 62 m above sea level at point coordinates 103º and 01º N latitude, and rubber plants plateau at an altitude of 806 m above sea level at point coordinates 101º and 02º N latitude. Age plains below its rubber trees start producing clones BPM 24 is 4 years, while the age of the same clone rubber plants in high dtaran start producing 8 years. Rubber latex production plant for low-lying lower than the production of latex rubber plant plateau.Keywords: characteristics, quality, physical and chemical, latex, rubber plants.